2010
DOI: 10.14411/eje.2010.062
|View full text |Cite
|
Sign up to set email alerts
|

Identification of limonene as a potential kairomone of the harlequin ladybird Harmonia axyridis (Coleoptera: Coccinellidae)

Abstract: Abstract. Chemical cues involved in both host location and oviposition by Harmonia axyridis Pallas (Coleoptera: Coccinellidae) were investigated in laboratory and field experiments. Among the five volatiles tested in a four-arm olfactometer ((E)--farnesene, -pinene, -caryophyllene, cis-3-hexen-1-ol, and limonene), gravid H. axyridis females were significantly attracted to limonene and -caryophyllene. These two chemicals also increased H. axyridis oviposition on plants. Attraction of H. axyridis towards limonen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 78 publications
0
31
0
Order By: Relevance
“…The only exception was the number of patch visits in which aphid enemies showed increased visits to plants at the exaggerated EBF amount compared to the control and natural EBF amount. This is not surprising, since it already has been demonstrated that application of exaggerated EBF amounts (e.g., 1 mg in dispensers or a release of 0.45 μg h −1 by slow releasers) can attract additional predators, such as syrphid flies, ladybirds, and parasitoid wasps (Aphidiidae) in agricultural fields, and can decrease the infestation pressure on a crop (Alhmedi et al 2010;Cui et al 2012). However, the use of EBF alone to control aphid populations without the presence of aphid enemies will not lead to a decrease in infestation rates on plants (Calabrese and Sorensen 1978).…”
Section: Discussionmentioning
confidence: 94%
“…The only exception was the number of patch visits in which aphid enemies showed increased visits to plants at the exaggerated EBF amount compared to the control and natural EBF amount. This is not surprising, since it already has been demonstrated that application of exaggerated EBF amounts (e.g., 1 mg in dispensers or a release of 0.45 μg h −1 by slow releasers) can attract additional predators, such as syrphid flies, ladybirds, and parasitoid wasps (Aphidiidae) in agricultural fields, and can decrease the infestation pressure on a crop (Alhmedi et al 2010;Cui et al 2012). However, the use of EBF alone to control aphid populations without the presence of aphid enemies will not lead to a decrease in infestation rates on plants (Calabrese and Sorensen 1978).…”
Section: Discussionmentioning
confidence: 94%
“…They may have different effects on natural enemies by attracting them and stimulating their oviposition. Such was observed in Harmonia axyridis Pallas (Coleoptera: Coccinellidae) females when exposed to a rubber septum infused with limonene (Alhmedi et al, 2010) or having no effect such observed in Episyrphus balteatus DeGeer (Diptera: Syrphidae) (Verheggen et al, 2008). Other studies have demonstrated that floral scent composition can influence pollinator behaviour and, simultaneously with visual cues, impact the plant-pollinator relationship (Raguso et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Some predators, such as the harlequin ladybird also use it as a cue to locate prey and oviposition sites [53,54]. Beta-caryophyllene was also the attractant for some herbivorous insects such as the weevil [55] and the damson hop aphid [56].…”
Section: Discussionmentioning
confidence: 99%